Inter relationship of plasma lipid profile parameters with plasma uric acid levels in psoriasis - S., Srinivas; Goudappala, Prashanthkumar; R. T., Kashinath (International Journal of Research in Dermatology, 2018)
Background: Psoriasis is a chronic immune mediated skin disease accompanied with disturbances in systemic lipid turnover. Hyperuricemia has been frequently observed as an additional complication in psoriasis. The relationship between the raised plasma lipid parameters and the uric acid levels in psoriasis need to be ascertained. A study was undertaken to assess the possible relationship of plasma lipid parameters with plasma uric acid levels in psoriasis and to relate any such relationship to psoriasis disease severity. Methods: Non arthritic psoriasis patients were randomly selected and were grouped into mild (Group 1), moderate (Group 2) as well as severe (Group 3) based on their PASI scores. Plasma lipid parameters and uric acid levels were assessed in these patients. Results: The results show a significant (p<0.001) parallel raise in plasma uric acid levels along with plasma lipid parameters with the severity of disease in these patients. Conclusions: A plasma uric acid level along with plasma total cholesterol and triacylglycerol levels fetch much information on the severity of psoriasis disease.